Organic zinc with moderate chelation strength enhances zinc absorption in the small intestine and expression of related transporters in the duodenum of broilers - Hu, Yun; Wang, Chuanlong; Wu, Wei; Qu, Yicheng; Zhang, Weiyun; Li, Ding; Zhu, Ling; Gao, Feiyu; Wu, Bingxin; Zhang, Liyang; Cui, Xiaoyan; Li, Tingting; et al. (Frontiers in Physiology, 2022)
Our previous study demonstrated that the absorption of zinc (Zn) from the organic Zn proteinate with moderate chelation strength was significantly higher than that of Zn from the inorganic Zn sulfate in the in situ ligated duodenal segment of broilers, but the underlying mechanisms are unknown. The present study aimed to determine the effect of the organic Zn with moderate chelation strength and the inorganic Zn on the Zn absorption in the small intestine and expression of related transporters in the duodenum of broilers. The Zn-deficient broilers (13-d-old) were fed with the Zn-unsupplemented basal diets (control) containing 25.72 and 25.64 mg Zn/kg by analysis or the basal diets supplemented with 60 mg Zn/kg as the Zn sulfate or the Zn proteinate with moderate chelation strength (Zn-Prot M) for 26 d. The results showed that the plasma Zn contents from hepatic portal vein of broilers at 28 d and 39 d of age were increased (P < 0.05) by Zn addition, and greater (P < 0.05) in the Zn-Prot M than in the Zn sulfate. On d 28, Zn addition upregulated (P < 0.05) mRNA expression of zinc transporter 1 (ZnT1), Zrt-irt-like protein 5 (ZIP5), y+L-type amino transporter 2 (y+LAT2) and b0,+-type amino acid transporter (rBAT), zinc transporter 4 (ZnT4) protein expression and zinc transporter 9 (ZnT9) mRNA and protein expression in the duodenum. Moreover, ZnT9 mRNA expression, ZnT4, ZIP5 and rBAT protein expression, zinc transporter 7 (ZnT7) and y+LAT2 mRNA and protein expression in the duodenum of broilers on 28 d were higher (P < 0.05) in the Zn-Prot M than in the Zn sulfate. On d 39, supplemental Zn increased (P < 0.05) peptide-transporter 1 (PepT1) mRNA expression and y+LAT2 protein expression, while the mRNA expression of ZnT7 and Zrt-irt-like protein 3 (ZIP3) were higher (P < 0.05) for the Zn-Prot M than for the Zn sulfate in the duodenum. It was concluded that the Zn-Prot M enhanced the Zn absorption in the small intestine partially via upregulating the expression of the ZnT4, ZnT7, ZnT9, ZIP3, ZIP5, y+LAT2 and rBAT in the duodenum of broilers.